2021
DOI: 10.3390/app11146359
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a PCM for a Vehicle’s Rooftop by Multicriteria Decision Methods and Simulation

Abstract: The automotive industry is one of the most contaminant; for this reason, solutions in efficient matter has been proposed over the years. This research contributes to this subject by evaluating the thermal comfort in the internal air of a vehicle by using a 20 mm layer of a phase-change material attached to the rooftop interior of a car. The phase-change material selection is based on a list of other materials proposed in previous research and chosen by multicriteria decision methods. In this sense, the materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…More information about this MCDM can be found in [24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Statistical Variation Methodsmentioning
confidence: 99%
“…More information about this MCDM can be found in [24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Statistical Variation Methodsmentioning
confidence: 99%
“…In another study, Nicolalde et al [9] reported that the use of a PCM layer of 20 mm can improve the thermal comfort in the vehicle, reducing the need to use the heater or the air conditioner. It was found that the PCM reduced the temperature of the air by 9 • C when heating and by 4 • C when the temperature dropped.…”
Section: Design and Applicationsmentioning
confidence: 99%
“…The choice of a PCM primarily depends on its characteristics, including the phase change temperature, the heat of fusion, the thermal conductivity, the density, and the specific heat capacity. [32][33][34][35][36][37]. The temperature range of PCMs that can be used in air conditioning systems is approximately 7-14 • C [38].…”
Section: Introductionmentioning
confidence: 99%